PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2022-2024 - Rasti Kristanti Daramean; Nugraeni Nugraeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research is motivated by the importance of firm value as an indicator reflecting investor perceptions of a company's performance and future prospects. In manufacturing companies, firm value is influenced by various internal factors, including firm size and profitability. This study aims to analyze the influence of firm size and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with a causal research design. The data used are secondary data in the form of annual financial reports of manufacturing companies for the period 2022–2024. The sample was determined using a purposive sampling method, resulting in 30 companies with a total of 90 observations. Data analysis was performed using descriptive statistics, classical assumption tests, and multiple linear regression analysis with a significance level of 5 percent. The results show that firm size and profitability partially have a positive and significant effect on firm value. Furthermore, the results of simultaneous testing indicate that firm size and profitability together have a significant effect on firm value. These findings indicate that companies with large asset scales and high profitability levels tend to have higher firm value in the eyes of investors